Accuracy of a CBCT-based virtual injection software for vessel detection during hepatic arterial embolization. Issue 150 (May 2022) - Ridouani, Fourat; Ghosn, Mario; Doustaly, Raphael; Gonzalez-Aguirre, Adrian J.; Ziv, Etay; Solomon, Stephen B.; Edward Boas, F.; Yarmohammadi, Hooman
Highlights: Virtual injection accurately simulated selective arterial injection and was ranked as clinically relevant in 89.2% ± 0.5 of investigated vessels. Interobserver agreement was substantial with a Fleiss' kappa = 0.79 (95% confidence interval = 0.73–0.84). Abstract: Purpose: To assess the accuracy, sensitivity, positive predictive value (PPV) and interobserver agreement of a virtual injection (VI) software that simulates selective arterial injection from nonselective cone-beam CT (CBCT) arteriography. Methods: From March 2019 to May 2020, 20 consecutive patients in whom a nonselective injected CBCT and a selective CT angiography (CTA) were completed in the same procedure, were retrospectively included. The position of the microcatheter tip used for selective CTA injection was identified. The VI was simulated from the exact same point on the nonselective CBCT and the two volumes were merged. VI was compared to the real injection on the selective CTA. Three interventional radiologists evaluated the accuracy using a 6-point scale (Perfect; Good; Fair; Incorrect Origin; False Negative; Non existing). Sensitivity, PPV, and Fleiss' kappa were calculated. Numerical variables were presented as means ± standard deviations. Results: Twenty procedures and 195 vessel segments were analyzed. Most vessels were 4th order (57/195; 29%) and 5th order (96/195; 49%). VI was classified as perfect to good in 96.8% ± 1.4 of 1st–3rd order arteries and in 83.4% ± 0.4 of 4th–5th order arteries. Interobserver agreement was substantial (Fleiss' kappa = 0.79; 95% confidence interval = 0.73–0.84, P  < 0.01). False negatives were reported with a mean of 9.4% ± 0.3. Average sensitivity was 90.6% ± 0.3 and average PPV was 92.7% ± 0.02. Fourteen false positives were noted. Conclusion: CBCT-based VI software accurately simulated distal injections in the liver with high sensitivity and a substantial interobserver agreement.